DEVELOPMENT OF AN ECONOMIC GROWTH DATA VISUALIZATION DASHBOARD FOR PALEMBANG CITY USING THE AGILE METHOD - Mutiara Marsa silvia; Muhammad Nasir (Kresnamedia Publisher, 2026)
The presentation of economic growth data for Palembang City on the official website of Badan Pusat Statistik (BPS) still faces challenges in terms of usability, navigation, and data visualization. The complex menu structure, poorly organized data presentation, and limited interactive features reduce efficiency in accessing and interpreting economic information. To date, there is no dedicated interactive dashboard that centrally integrates and visualizes Gross Regional Domestic Product (GRDP) data for Palembang City in a user-oriented manner, creating a gap in the provision of accessible regional economic analysis tools. This study aims to develop an Economic Growth Data Visualization Dashboard for Palembang City to present GRDP data in a clearer, more interactive, and user-friendly format. The system was developed using the Agile Development method, consisting of planning, design, development, testing, and evaluation stages. The dashboard was built using Next.js as the frontend framework and MySQL as the database management system. It presents GRDP data at current prices (ADHB), constant prices (ADHK), expenditure components, and business sector categories through interactive charts and dynamic tables. Black-Box testing confirmed that all system features functioned properly. Usability testing using the System Usability Scale (SUS) with 50 respondents resulted in a score of 84.8, categorized as Excellent. The system is feasible as a decision-support tool for regional economic data analysis.